2020
DOI: 10.3892/ijmm.2020.4778
|View full text |Cite
|
Sign up to set email alerts
|

TGF‑β1‑induced autophagy activates hepatic stellate cells via the ERK and JNK signaling pathways

Abstract: Transforming growth factor β1 (TGF-β1) is one of the most important fibrogenic factors promoting the activation of hepatic stellate cells (HScs). Autophagy is a process used by cells to degrade and recycle cellular proteins. Although TGF-β1 induces autophagy in several other cellular systems, the association between its effect on fibrogenesis and autophagy in HScs have not been determined. Liver tissues from c57BL/6 mice and the mouse HSc line JS1 were analyzed. Acute and chronic liver injury models were induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 52 publications
6
33
0
Order By: Relevance
“…TGF-β1 was reported to be the key cytokine in the process of HSC activation and liver fibrosis ( 17 ). The present study investigated the role of miR-21-5p in TGF-β1-induced liver fibrosis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…TGF-β1 was reported to be the key cytokine in the process of HSC activation and liver fibrosis ( 17 ). The present study investigated the role of miR-21-5p in TGF-β1-induced liver fibrosis.…”
Section: Resultsmentioning
confidence: 99%
“…In physiological conditions, quiescent-like HSCs exhibit necessary effects on lipid metabolism, maintaining the balance of extracellular matrix (ECM) production and degradation ( 16 ). When liver injury occurs, HSCs are activated by cytokines including TGF-β1 secreted by a variety of cells in the liver ( 17 ). These activated HSCs produce excessive ECM deposited in liver tissue disrupting liver structure leading to liver fibrogenesis ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGF-β-mediated ROS production, in a NOX4-dependent pathway, induces autophagy in epithelial cells [136]. During liver fibrosis, TGF-β1 induces autophagy through activation of the ERK and JNK signaling pathways [137], which play essential roles in regulating autophagic processes [138], and autophagy is involved in the activation of HSCs [137]. In fact, using cell culture and/or different animal models, numerous studies have shown that autophagy is enhanced during the fibrogenic process and have provided specific evidence to pinpoint the fundamental role of autophagy in HSCs activation [139].…”
Section: Noxs In Hccmentioning
confidence: 99%
“…We previously found that LX-2 cells mount an inflammatory response and upregulate fibrosis indicators in response to LPS. Here, we focused on the MAPK/ERK/JNK signaling, which controls various processes in HSCs (20)(21)(22). Western blot analysis revealed elevated phosphorylated JNK and phosphorylated ERK levels in LX-2 cells relative to control (Figure 2).…”
Section: Mapk/erk/jnk Pathway Levels Are Elevated In Lx-2 Cells In Response To Lpsmentioning
confidence: 99%